Pengaruh Zakat terhadap Kinerja Perusahaan (Studi Empiris pada Bank Umum Syariah di Indonesia) - Rika Febby Rhamadhani (State Institute of Islamic Studies (IAIN) Palu, 2016)
This study aims to determine and analyze the effect zakat on corporate performance in sharia banks in Indonesia. The data used in this research are secondary data obtained from the financial statements of each site Islamic Banks in Indonesia gathered through technical documentation in the form of documents and annual financial reports and other data related to this study. The sampling technique used purposive sampling and analytical methods used simple regression analysis. These results indicate significant influence between zakat on the corporate performance in sharia banks in Indonesia. This study recommend are the corporate does not to be afraid of issuing zakat, because in Islam, Allah already guarantee that Zakat issued will not reduce property and zakat is also an expense that can be deducted for taxable income and further research is expected to add the study period and a number of larger samples in order to obtain more accurate research results